Adsorption of Thiophene in MCM-22 Zeolite by Grand Canonical Monte Carlo Simulation - Xuan, Li-Chun; Li, Ming-Xia; Pan, Qing-Jiang; Zhang, Guo (Asian Journal of Chemistry, 2012)
The grand canonical ensemble Monte Carlo simulation was employed for investigating adsorption behaviour of thiophene in MCM-22 zeolite, the practice from which we gain some information of adsorption isotherm, heat of adsorption and distribution of thiophene. Result shows that the adsorption and distribution of thiophene are greatly affected by temperature and pressure and heat of adsorption is hardly affected by temperature and pressure. Thiophene distribute widely in 10-MR pore and 12-MR supercage of MCM-22 zeolite and their preferential adsorption positions are at upper and lower part of supercage and in independent 10-MR pore. Through the investigation on the calculation of potential energy surface produced by thiophene crossing 10-MR window, we gain the information that thiophene can migrate freely within 12-MR supercage and that when thiophene migrates from one supercage to its adjacent supercage, high potential energy employed by its crossing 10-MR window needed to be overcomed, potential energy is 100 kJ/mol.